Occupational accidents among middle and high school students of the state of São Paulo, Brazil - Frida M Fischer; Ignez S Martins; Denize C Oliveira; Liliane R Teixeira; Maria do Rosario D Latorre; Sharon P Cooper
OBJECTIVES: To estimate the prevalence of occupational injuries and identify their risk factors among students in two municipalities. METHODS: A cross-sectional survey was conducted in public schools of the municipalities of Santo Antonio do Pinhal and Monteiro Lobato, Brazil. A stratified probabilistic sample was drawn from public middle and high schools of the study municipalities. A total of 781 students aged 11 to 19 years participated in the study. Students attending middle and high school answered a comprehensive questionnaire on living and working conditions, as well as aspects of work injuries, and health conditions. Multiple logistic regression models were fitted to estimate risk factors of previous and present occupational injuries. RESULTS: Of 781 students, 604 previously had or currently have jobs and 47% reported previous injuries. Among current workers (n=555), 38% reported injuries on their current job. Risk factors for work injuries with statistically significant odds ratio >2.0 included attending evening school, working as a housekeeper, waiter or brickmaker, and with potentially dangerous machines. CONCLUSIONS: The study results reinforce the need of restricting adolescent work and support communities to implement social promotion programs.